Analisis Kesulitan Belajar Siswa Dalam Menyelesaikan Soal Asesmen Kompetensi Minimum Di SDN Pondok Cabe Ilir 01 - Siti Sefiyati Hasna Hanifah; Linda Astriani (Pusat Riset dan Inovasi Nasional, 2024)
Learning difficulties experienced by students are based on the covid-19 pandemic which requires students to study at home so that students do not understand geometry material. The purpose of this study was to determine the factors that cause students' learning difficulties in solving AKM problems and to find out students' learning difficulties in solving AKM problems. This research was conducted at SDN Pondok Cabe Ilir 01 in the 2022/2023 academic year with 3 research subjects based on their categories, namely high, medium, and low. This type of research is descriptive qualitative. Data collection techniques used observation, tests, interviews, and documentation. The test amounted to 15 questions. Data analysis techniques are data reduction, data presentation, and conclusions. The results showed that out of 27 students in the high category there were 3 students, in the medium category there were 14 students, and in the low category there were 10 students. The high category had learning difficulties in the use of principles and the causal factor came from external factors because they felt the teacher did not explain well, the medium category had learning difficulties in the use of concepts and the causal factor came from internal factors because they did not pay attention to the teacher when teaching, and the low category had learning difficulties in verbal problems and the causal factor came from internal factors because they did not dare to ask when they did not understand. The results of the study are expected to be useful for school principals, teachers, students, researchers, and other researchers.The results of this study are expected to be useful for principals, teachers, students, researchers, and other researchers